Discursos e práticas em torno da conservação da biodiversidade nas ações da Itaipu Binacional (1975-1987) - Ziober, Beatriz Ramalho (2011)
The main objective of this dissertation is to write about the Plans to Conservate the Enviroment that were formulated by Itaipu Binational when this place was built. It is important to realize what took this enterprise to adopt the politics of "concern" about the nature, in a period which the developing plans of evolution and progress of the country were present in the imagination of brazilian people and the military presidents' politics. At the same time that the politics in Brazil were marked by the search of progress in military's dictatorship, all enviroment problems started to show off in international scenary, mainly after the Stockholm's Conference, in 1972. Realizing how much the international environment politics influenciated Brazil on this period is fundamental to analyze Itaipu's plans and to understand if they were really viable.